Can adolescent well-being be promoted online? Evaluating the effectiveness of a school-based program - Kuusisto, Suvi (My University, 2019)
Recent research has shown the potential of online programs targeting adolescents’ well-being. Research literature also recommends that interventions should be school-based and focus on promoting mental health rather than preventing mental health problems. Accordingly, the Opintokamu course is an online course that aims to promote the well-being of upper secondary education students through three self-study themes: studying, emotional well-being, and social relationships. The present study examined the effectiveness of the Opintokamu course. The study included 19 outcomes from the three themes of Opintokamu. The hypothesis was that well-being within these outcomes would increase among the participants in the intervention group, who had completed the course, compared to the participants in the control group, who had no access to the Opintokamu material. The data were collected in four occasions from eight intervention and eight control schools in Finland. The final sample consisted of 840 upper secondary education students of which 168 had completed the Opintokamu course. For each participant in the intervention group, four matched controls were obtained from the data, with the total of 672 control participants included in the study. The results suggested that the effectiveness of the Opintokamu course is limited to reducing exhaustion. Altogether, the course seems to be insufficient to increase adolescents’ well-being within a school year as measured with the variables included. Future directions should include examination of the course effects on emotional literacy and skills related to the course topics, as well as qualitative studies on adolescents’ perceptions of the course and its potential benefits.
Keywords: Opintokamu, online program, online course, adolescents, well-being